Relationship between pulmonary function and the degree of spinal deformity among adolescent idiopathic scoliosis (AIS) patients - Johari, Joehaimey; Nor, Sobri; Lam, Andrew; Omar, Ahmad Sabri; Abdullah, Ahmad Tajudin; Ab Rahman, Azriani; Sharifudin, Mohd Ariff; Yusof, Mohd Imran (2013)
Background: A retrospective record review was conducted among patients aged between 13 to 24 years, diagnosed as adolescent idiopathic scoliosis (AIS) and admitted at Hospital Raja Perempuan Zainab II for surgical intervention from year 2000 to 2013.